(untitled) (International Journal of Engineering and Computer Science, 2014)
The fundamental requirements for any wireless sensor network (WSN) are network life time, resource efficiency and dependability of a trust system. We are applying a clustering scheme considering mobility to minimize the number of nodes that moves away from the current cluster head before next cluster formation. This approach improves network life time and energy consumption. In addition, we use trust decision-making scheme based on the node’s identities in the clustered MWSNs to send data packets to sink. It facilitates energy-saving by canceling feedback between cluster members (CMs) or between cluster heads (CHs), which is suitable for WSNs. This approach can significantly improve system efficiency, while reducing the effect of malicious nodes, selfish, and faulty CHs of networking consumption. Theory as well as simulation results show that clustering scheme improves network lifetime and dependable trust decision making scheme demands less memory and communication overhead compared with the current typical trust systems for WSNs.